Palaeopsylla (Palaeopsylla) aysenurae n. sp., a new ctenophthalmid flea (Siphonaptera: Ctenophthalmidae) from Turkey - Keskin, Adem; Beaucournu, Jean-Claude (Zootaxa, 2019)
A new flea species, Palaeopsylla (Palaeopsylla) aysenurae n. sp., belonging to the Palaeopsylla minor-group is described and illustrated. Specimens (seven males and nine females) of the new species were collected from Talpa levantis Thomas, 1906 (Mammalia: Talpidae) from Trabzon province of Turkey. An identification key to all known species of the Palaeopsylla minor-group is provided.